2021
DOI: 10.1186/s13102-020-00230-8
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity compression garments use by athletes: why, how often, and perceived benefit

Abstract: Background Studies on the benefits of lower extremity compression garments (CGs) have focused on their effects on post-exercise recovery and performance improvement. Less is known about why athletes actually use CGs, the frequency with which they use them, and perceived benefits from using CGs. The purpose of this study was to investigate which athletes use CGs, why athletes use CGs, when CGs are worn by athletes, and, in case of an injury or injury prevention, for which injuries CGs are used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The low frequency of use of cold water immersion and compression garments in our study may be attributed to the low awareness of athletes and coaches about their possible effectiveness. Compression garments are widely used by endurance athletes in other countries [ 25 ]. In a meta-analysis by Machado et al, diving in cold water for 60 min after the end of the exercise was also confirmed as a means of reducing the severity of DOMS (when compared with passive recovery) and it was concluded that there is a dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The low frequency of use of cold water immersion and compression garments in our study may be attributed to the low awareness of athletes and coaches about their possible effectiveness. Compression garments are widely used by endurance athletes in other countries [ 25 ]. In a meta-analysis by Machado et al, diving in cold water for 60 min after the end of the exercise was also confirmed as a means of reducing the severity of DOMS (when compared with passive recovery) and it was concluded that there is a dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that endurance athletes commonly use lower extremity compression garments especially runners [ 30 ]. However, this was not the case in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not the case in the current study. Athletes who wear compression garments for recovery report perceived faster recovery and improvements in sports performance [ 30 ]. In the current study, athletes value compression garments more in competition than in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing the existing research, we know that the research at home and abroad mainly focuses on the application research of tight sportswear, such as energy metabolism, muscle function, mechanical performance, drag reduction effect, injury protection and sports medicine, and they have made a certain foundation. [32][33][34] However, as the clothes that cling to human skin, the comfort of tight sportswear is also a key performance that cannot be ignored. Comfort evaluation of tight sportswear is mainly judged by human senses, and the process of analyzing comfort information is extremely complicated, 35 which is related to whether clothing and human body meet a series of requirements.…”
mentioning
confidence: 99%